Optimasi Penjadwalan Mata Pelajaran menggunakan Constraint Programming - Nurcahyawati, Vivine; Muhamad Risqiwahid; Achmad Arrosyidi (Jurnal Informatika dan Teknologi Informasi, 2023)
Schools are educational institutions that have teaching and learning activities, one of the teaching and learning processes is scheduling subjects carried out by the Deputy Principal Curriculum to arrange subject schedules every school year once. The preparation of the subject schedule used today still uses Microsoft Excel, causing problems including the crash schedule, the number of classes taught exceeds the teaching hours, and complications in arranging the schedule if there is a change of schedule. The solution to the problem above is to create subject scheduling applications in website -based schools using constraint programming and stages of system development using waterfall. The results of the study obtained in this study showed that the application succeeded in forming subject schedules that schools can use. Furthermore, the application can be in accordance with the boundaries related to the specified scheduling. As well as applications can help the preparation of subjects optimally with no 100%crresses. The system in the application requires a maximum of 10 minutes for the schedule creation process. Keywords: Scheduling, Constraint Programming, Waterfall, Course